2002
DOI: 10.14411/fp.2002.036
|View full text |Cite
|
Sign up to set email alerts
|

Survey of actinosporean types (Myxozoa) belonging to seven collective groups found in a freshwater salmon farm in Northern Scotland

Abstract: Abstract.A study of the actinosporean fauna of oligochaetes from a freshwater salmon farm in Northern Scotland was carried out from October 1996 to August 1998. Following the examination of 28,387 oligochaete worms belonging to the families Tubificidae, Lumbriculidae, Naididae and Enchytraeidae, five types of echinactinomyxon (four previously described), six types of raabeia (five previously described), three types of synactinomyxon (all previously described), four types of aurantiactinomyxon (three previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 30 publications
3
22
0
2
Order By: Relevance
“…The aurantiactinomyxon is a taxon-rich collective group composed of more than 20 actinospore types in previous studies (Styer et al 1991;Yokoyam et al 1993;Trouillier et al 1996;McGeorge et al 1997;El-Mansy et al 1998b, c;Xiao and Desser 1998b, c;Székely et al 2000Székely et al , 2003Székely et al , 2004Negredo and Mulcahy 2001;Özer et al 2002;Oumouna et al 2003;Holzer et al 2004;Marcucci et al 2009). The aurantiactinomyxon type examined differed from these types with much longer, slight downward curved and spines or rays-like caudal process, pointed process tips and 64 secondary cells in sporoplasm.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The aurantiactinomyxon is a taxon-rich collective group composed of more than 20 actinospore types in previous studies (Styer et al 1991;Yokoyam et al 1993;Trouillier et al 1996;McGeorge et al 1997;El-Mansy et al 1998b, c;Xiao and Desser 1998b, c;Székely et al 2000Székely et al , 2003Székely et al , 2004Negredo and Mulcahy 2001;Özer et al 2002;Oumouna et al 2003;Holzer et al 2004;Marcucci et al 2009). The aurantiactinomyxon type examined differed from these types with much longer, slight downward curved and spines or rays-like caudal process, pointed process tips and 64 secondary cells in sporoplasm.…”
Section: Discussionmentioning
confidence: 94%
“…Özer et al 2002;Lowers and Bartholomew 2003;Oumouna et al 2003). The high morphological variability of some triactinomyxon types that have caused the correct identifications was difficult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the actinosporean types, which are morphologically and genetically the closest to the synactinomyxon type reported in this paper, did not possess fully identical dimensions: e.g. Synactinomyxon longicauda (Marques & Ormieres 1982, Özer et al 2002 Table 2. Comparison of synactinomyxon types described in the special literature.…”
Section: Discussionmentioning
confidence: 67%
“…After the pioneering work of Š tolc (1899), several authors have reported on synactinomyxon types or species from natural waters (Janiszewska 1955, Marques 1984, Hamilton & Canning 1987, Xiao & Desser 1998, Özer et al 2002 (Table 2). The synactinomyxon type described in this study differed substantially, in at least one of its dimensions, from the 8 synactinomyxon types recorded previously.…”
Section: Discussionmentioning
confidence: 99%